PENGEMBANGAN MEDIA PEMBELAJARAN ENGINE CUTTING HONDA GRAND SEBAGAI MEDIA PEMBELAJARAN MULTI KOMPETENSI - Rahma, Nur syafiqah; Amiruddin, Muhamad (Journal of Automotive Technology Vocational Education, 2024)
Research on the development of Honda Grand engine cutting learning media as a multi-competency learning media aims to design and determine the feasibility of engine cutting learning media as a tool for student understanding in multi-competency learning activities in subjects 1) Automotive basics 2) Motor gasoline 3) motorcycle. This study uses the Research and Development research method to develop and test products to be developed, the results of this study indicate the average percentage of validation of Honda grand engine cutting learning media as a multi-competency learning media from functional and feasibility tests by media expert lecturers and material experts is 76% based on the feasibility category table, the validation results are included in the feasible category and based on the results of functional tests by students, namely obtaining an average percentage of 88.2% including in the very feasible category.  Thus, based on the results of the percentage of feasibility scores obtained above, it can be said that the Honda grand engine cutting learning media as a multi-competency learning media is feasible to use and develop.   Keywords: development, engine cutting Honda Grand, R&D.